Rotational Sweep Rotating Zone Plate Sequence - 李桂苓; 周志河 (Tongxin xuebao)
This paper presents the principle and method of setting up a mathematical model of rotational sweep rotating zone plate in polar coordinate system. The new zone plate developed contains all spatial fraquencies,and can truly rotate at different speeds.There is quantitative relationship between the zone plate parameters and the time-space characteristics of the image,and the precorrection on the pixel shape is also provided. The data of the zone plate are stored in magnetic tape conforming international exchange standard.Experiments show that the new zone plate can be used to evaluate HDTV system.